The size of the loggerhead nesting females in the Cape Verde islands - Ballell-Valls, Lluis; López-Jurado, Luis Felipe (2016)
The recently discovered nesting colony of Caretta caretta at the island ofBoavista (Cape Verde Islands, West Africa, FIGURE 1) is being subject ofresearch since 1998. A total number of 1,391 different females have been tagged during the 1998, 1999 and 2000 nesting seasons. Although more data are needed, these islands may represent one ofthe most important populations for the species in the North Atlantic (Brongersma, 1982; Ross, 1995; López-Jurado & Andreu, 1998). The present study shows a comparative analysis between the morphometric data collected at Boavista during the last 2000 nesting season and those recorded in the 1998 and 1999 seasons. These data have also been contrasted with those from other loggerhead nesting populations around the world for possible differences.